PENGARUH LINGKUNGAN KERJA DAN BEBAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. CITRA SULAWESI SEJAHTERA (DEPARTEMENT STORE) - Fajrul Hakim (J-MSDM (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2024)
The Influence of Work Environment and Workload on Employee Job Satisfaction at PT. Citrasulawesi Sejahtera. The purpose of this research is to test and analyze the variables that have the most dominant influence, namely work environment variables and workload on employee job satisfaction variables, where this research uses a quantitative approach with the research population of employees at PT. Citrasulawesi Sejahtera has 150 employees. And a sample of 60 respondents with multiple linear regression analysis method using the SPSS application. The results of this research indicate that the Work Environment and Workload variables have a significant positive effect on employee job satisfaction.